2022
DOI: 10.1007/s12237-022-01111-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Ecosystem Experiment Illustrates Short Timescale Hydrodynamic, Light, and Nutrient Control of Primary Production in a Terminal Slough

Abstract: Estuaries are among the most productive of aquatic ecosystems. Yet the collective understanding of patterns and drivers of primary production in estuaries is incomplete, in part due to complex hydrodynamics and multiple controlling factors that vary at a range of temporal and spatial scales. A whole-ecosystem experiment was conducted in a deep, pelagically dominated terminal channel of the Sacramento-San Joaquin Delta (California, USA) that seasonally appears to become nitrogen limited, to test whether adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Previous work in the SFE has demonstrated light limitation of phytoplankton productivity due to high turbidity (Alpine & Cloern, 1988; Cloern, 1987), though field studies have shown discrepancies between productivity predicted by light models compared to in situ measurements in certain habitats (Parker et al, 2012; Stumpner, Bergamaschi, et al, 2020). Given this context, we expected to see negative effects of turbidity on phytoplankton, and only weak effects of nitrate in the landward reaches of the DWSC where nitrogen concentrations can become limiting in summer (Loken et al, 2022). However, only cryptophytes showed the expected negative relationship with turbidity (Figure 4), whereas bacillariophyte biomass was positively associated with turbidity in all three zones, and chlorophytes were positively associated in the HE zone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work in the SFE has demonstrated light limitation of phytoplankton productivity due to high turbidity (Alpine & Cloern, 1988; Cloern, 1987), though field studies have shown discrepancies between productivity predicted by light models compared to in situ measurements in certain habitats (Parker et al, 2012; Stumpner, Bergamaschi, et al, 2020). Given this context, we expected to see negative effects of turbidity on phytoplankton, and only weak effects of nitrate in the landward reaches of the DWSC where nitrogen concentrations can become limiting in summer (Loken et al, 2022). However, only cryptophytes showed the expected negative relationship with turbidity (Figure 4), whereas bacillariophyte biomass was positively associated with turbidity in all three zones, and chlorophytes were positively associated in the HE zone.…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations between nitrate and chlorophytes may reflect the fact that chlorophyte biovolume in the landward reaches is highest in summer, when dissolved inorganic nitrogen concentrations are lower. In situ measurements and incubation experiments suggest nitrogen‐limitation in the landward reaches of the DWSC during stratified periods of summer (Loken et al, 2022), but monthly sampling is insufficient to capture rapid phytoplankton blooms in response to nutrient inputs (Dugdale et al, 2007) and short‐time scale variation in hydrodynamics (Lenoch et al, 2021). Overall, the associations of nitrate and phosphate with phytoplankton were small and frequently non‐significant, suggesting that at seasonal and inter‐annual time scales other drivers were more important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations